Service-oriented control architecture for reconfigurable production systems - Mendes, João M. (2009)
Evolvable and collaborative production systems are becoming an emergent paradigm towards flexibility and automatic re-configurability. The reconfiguration of those systems requires the existence of distributed and modular control components that interact in order to accomplish control activities. This paper focuses on service-oriented production systems, which behavior is regulated by the coordination of services that are provided and required by control components with different roles. Internally, these components are independent of the implementations, but an internal modular and event based structure is presented. Individual control and interaction is achieved by using embedded or inter-service control processes for which High-Level Petri Nets are proposed. Supporting the predefined control, decision support systems are used to provide conflict resolution and other decision-making functions.